ADSORPTIVE DESULFURIZATION OF DIBENZOTHIOPHENE USING ALUMINUM-IMPREGNATED PALM KERNEL SHELL ACTIVATED CARBON: EQUILIBRIUM AND KINETIC STUDY (REMUNOM, 2026)
The presence of sulfur-containing compounds in petroleum-derived fuels represents a major environmental and technological concern due to SO₂ formation during combustion and catalyst deactivation in refining processes. In this context, adsorptive desulfurization has been investigated as a complementary alternative to conventional hydrodesulfurization. In this work, the removal of dibenzothiophene (DBT) from n-heptane by adsorption onto activated carbon obtained from palm kernel shell, previously oxidized with nitric acid and impregnated with aluminum (CACD-Al), was evaluated. Equilibrium and kinetic experiments were carried out in a closed batch system at different temperatures. The equilibrium data were fitted to the Langmuir, Freundlich, BET, Radke-Prausnitz and Sips isotherm models, with the Sips model providing the best statistical agreement, indicating surface heterogeneity. A maximum adsorption capacity of approximately 0.66 mmol g⁻¹ at 30 °C was obtained, which is higher than or comparable to values reported in the literature for activated carbons applied to DBT removal. The kinetic behavior was satisfactorily described by the Homogeneous Surface Diffusion Model (HSDM), revealing that intraparticle diffusion is the rate-controlling step. The results demonstrate that CACD-Al is a promising low-cost adsorbent for the adsorptive desulfurization of thiophenic compounds, with potential application as a complementary step to conventional sulfur removal processes in liquid fuels.